Esophageal squamous cell carcinoma and adenocarcinoma in Malaysia – Pooled data from upper gastrointestinal centers in a multiethnic Asian population. (October 2022) - Lim, Raymond Zhun Ming; Mahendran, Hans Alexander; ,; Beng Ng, Chong; Yean Low, Kuan; Thannimalai, Sekkapan; Woon Ngo, Choon; Kosai Nik Mahmood, Nik Ritzal; Rajan, Reynu; Aznan Shuhaili, Mohamad; Bin Mohd Salleh, Ahmad Sudirman; Gurunathan, Ramesh A/L K.; et al.
Abstract: Background: Esophageal cancer is the sixth leading cause of cancer death worldwide with considerable geographical histological variation There is a paucity of data in esophageal cancer in demographics, histology, and survival among the multi-ethnic Malaysian population. This paper is a review of esophageal cancer epidemiology and survival among esophageal cancer patients from data collected by the Malaysian Upper Gastrointestinal Surgical Society. Methods: This is a multicenter retrospective observational study of esophageal cancer patients from six upper gastrointestinal surgical centers in Malaysia between 2005 and 2019. Patient characteristics, histological type and stage were compared and survival analyzed. Results: There were 820 patients with esophageal cancer included, where 442 (53.9 %) cases had squamous cell carcinoma (SCC) and 378 (46.1 %) had adenocarcinomas (AC). Malays were the predominant ethnicity with AC (66.7 %) while Indians were the ethnic majority (74.6 %) with SCC. Majority of patients (56.8 %) presented as stage IV disease. Overall, the 1-, 3-, and 5-years' survival were 35.8 %, 13.8 % and 11.0 %, respectively. Surgical resection with curative intent yielded the best 5-year survival (29.4 %). Intervention in stage IV AC yielded superior survival when compared to SCC (median survival, 7.9 months vs 4.8 months; p, 0.018) Our series demonstrated an increase in AC to SCC over the last 15 years. Conclusions: There was an ethnic preponderance seen between different histology in this region, not previously discussed. An increase in AC was observed over the last 15 years. Late diagnosis seen in most patients imparts poor prognosis as curative surgery affords the best outcome. Highlight: Histology preponderance varies between different Asian ethnicities in Malaysia. There is a regional increase in proportion of esophageal adenocarcinoma over the past 15 years. Most patients in this region still present late.